2016
DOI: 10.1371/journal.pone.0154102
|View full text |Cite
|
Sign up to set email alerts
|

Short Chain Fatty Acids (SCFA) Reprogram Gene Expression in Human Malignant Epithelial and Lymphoid Cells

Abstract: The effect of short chain fatty acids (SCFAs) on gene expression in human, malignant cell lines was investigated, with a focus on signaling pathways. The commensal microbial flora produce high levels of SCFAs with established physiologic effects in humans. The most abundant SCFA metabolite in the human microflora is n-butyric acid. It is well known to activate endogenous latent Epstein-Barr virus (EBV), that was used as a reference read out system and extended to EBV+ epithelial cancer cell lines. N-butyric ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…SCFAs affect the immune system by modifying gene expression profiles (68,69), cell chemotaxis (70,71), differentiation (54)(55)(56), proliferation (72)(73)(74), and apoptosis (75,76). In addition, SCFAs inhibit histone deacetylases (HDACs) and stimulate histone acetyltransferase (53, 56, 77, 78) ( Figure 1).…”
Section: Sources and Mechanisms Of Scfa Productionmentioning
confidence: 99%
“…SCFAs affect the immune system by modifying gene expression profiles (68,69), cell chemotaxis (70,71), differentiation (54)(55)(56), proliferation (72)(73)(74), and apoptosis (75,76). In addition, SCFAs inhibit histone deacetylases (HDACs) and stimulate histone acetyltransferase (53, 56, 77, 78) ( Figure 1).…”
Section: Sources and Mechanisms Of Scfa Productionmentioning
confidence: 99%
“…Cells are affected by SCFAs, through binding to cell surface receptors which result in regulation of cell proliferation and differentiation. Individual SCFAs can enter cells through specific transporters and directly affect cellular metabolism, thus influencing cellular energy and signaling pathways . Studies have also found that SCFAs can modulate the immune response by regulating the size and function of the colonic Treg pool that can protect against colitis and intestinal inflammation in a FFAR2‐dependent manner in mice .…”
Section: Introductionmentioning
confidence: 99%
“…We show that the short-term (15–30 days) daily consumption of one high-fiber bar significantly increased the beneficial microbial metabolites SCFA, along with a durable change in the Firmicutes-to-Bacteroidetes ratio [ 17 ], up to 40 days after the dietary intervention stopped. This is of relevance, as it was shown that SCFAs affected the immune system during inflammatory diseases by modifying gene expression profiles [ 18 , 19 ], cell chemotaxis [ 20 , 21 ], differentiation [ 6 , 22 , 23 ], proliferation [ 24 , 25 , 26 ] and apoptosis [ 27 , 28 ]. In addition, SCFAs inhibit histone deacetylases (HDACs) and stimulate histone acetyltransferase [ 6 , 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%